OPERATING PLAN OF BUSINESS COUNCIL ON INDOOR AIR, INC (Tufts Archival Research Center, 2007)
Draft; Draft of Business Council on Indoor Air (BCIA) operating plan. Provides history on the indoor air quality issue. Outlines current status of indoor air quality legislation. Lists actions necessary now. Includes mission statement, list of primary targets and secondary targets, and summarizes strategies and actions to be taken.